PENGARUH PENERAPAN SISTEM AKUNTANSI PEMERINTAH DAERAH, PENGENDALIAN INTERN DAN SISTEM PELAPORAN TERHADAP AKUNTABILITAS KINERJA INSTANSI PEMERINTAH (Studi Persepsian Pada Satuan Kerja Perangkat Daerah Kota Pekanbaru) - Dina Afrina; Ria Nelly Sari; Lila Anggraini (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Ekonomi, 2015)
This study aimed to examine the influence of the implementation local government accounting system, internal control and reporting system at the accountability of public institutions. This study were conducted at government agencies of Pekanbaru city.The population at this study were employed who worked in the Pekanbaru city. The sampling method used in this study is purposive sampling method. The respondent in this study is the head of SKPD, the head of financial and staff financial. The sample used in this study were 90 respondents. The hypotheses then tested is multiple linear regression analysis by using SPSS version 20.0The result of this study indicated that the implementation local government accounting system, internal control and reporting system has significantly effect on performance accountability of public institutions. The magnitude of the effect (R2) the implementation local government accounting system, internal control and reporting system on the performance accountability of public institutions was 63,5%. While the remaining 36,5% is influenced by other independent variabel that are not observed in this study.Keywords: accounting system, internal control, reporting, and accountability